1992
DOI: 10.1093/bja/69.4.341
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Respiratory Changes After Cholecystectomy Performed via Laparotomy or Laparoscopy

Abstract: We have compared metabolic and respiratory changes after laparoscopic cholecystectomy (n = 15) with those after open cholecystectomy (n = 15). The durations of postoperative i.v. therapy, fasting and hospital stay were significantly shorter in the laparoscopy group. During the first and second days after operation, analgesic consumption but not pain scores (visual analogue scale) were significantly smaller after laparoscopy, while vital capacity, forced expiratory volume in 1 s, and PaO2 were significantly gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
155
1
9

Year Published

1994
1994
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(175 citation statements)
references
References 15 publications
6
155
1
9
Order By: Relevance
“…The IL-6 response to surgery reflects the extent of tissue damage. It was observed that the increase in IL-6 after various surgical procedures is related to the severity of surgical trauma [23], while IL-6 production is decreased when surgery is undertaken using laparoscopic techniques [24]. Jakeways et al [25] demonstrated significantly less increase in mean IL-6 and C-reactive protein concentrations after laparoscopic compared with open cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-6 response to surgery reflects the extent of tissue damage. It was observed that the increase in IL-6 after various surgical procedures is related to the severity of surgical trauma [23], while IL-6 production is decreased when surgery is undertaken using laparoscopic techniques [24]. Jakeways et al [25] demonstrated significantly less increase in mean IL-6 and C-reactive protein concentrations after laparoscopic compared with open cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Durante o PPC, o efeito mecânico da insuflação comprime os vasos de capacitância (sistema venoso) e os vasos de resistência (sistema arterial) levando a aumento significativo das pressões de enchimento cardíaco, nas câmaras esquerda e direita 34,60,61 . O aumento da PIA leva a um aumento da pressão intratoráci-ca ocasionando um aumento da pressão sobre as câmaras cardíacas, com aumento da pressão do átrio direito e da pressão da artéria pulmonar ocluida 28,62 . O aumento da PIA tem efeito bifásico sobre o retorno venoso com um aumento da compressão dos vasos de capacitância intra-abdominais, seguido da impedância do retorno venoso do abdômen para os membros inferiores.…”
Section: Resultsunclassified
“…During CPP, the mechanical inflation effect compresses capacitance vessels (venous system) and resistance vessels (arterial system) leading to significant increase in filling pressures in both left and right chambers 34,60,61 . IAP increase leads to intra-thoracic pressure increase with consequent pressure increase in cardiac chambers, with increased right atrium pressure and pulmonary capillary wedge pressure 28,62 . IAP increase has a two-phase effect on venous return, with increased compression of intra-abdominal capacitance vessels, followed by the impedance of abdominal venous re-turn to lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…Reason attributed to actual cause of pain due to carbon dioxide is cellular death caused by combination of temperature change from the gas at 21°C and drying effect of gas in abdomen [10]. It may be transient or persistent for up to 3 days after laparoscopic cholecystectomy [11]. This increases patient's morbidity and analgesic requirement.…”
Section: Introductionmentioning
confidence: 99%